1999
DOI: 10.1034/j.1399-0039.1999.530305.x
|View full text |Cite
|
Sign up to set email alerts
|

β2‐μ‐free HLA class I heavy chain levels in sera of healthy individuals. Lack of association with β2‐μ‐associated HLA class I heavy chain levels and HLA phenotype

Abstract: We have applied a double-determinant immune assay (DDIA) to measure soluble beta2-microglobulin (beta2-micro)-free HLA class I heavy chains in serum. The mean concentration of beta2-micro-free HLA class I heavy chains in serum from 120 healthy subjects was 0.21+/-0.24 microg/ml. The individual serum levels of beta2-micro-free HLA class I heavy chains had a wide distribution, did not seem to be related with HLA phenotype, were stable over time and did not change with age. The serum levels of soluble beta2-micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
0
11
1
Order By: Relevance
“…However, in a previous study Puppo et al [36] using a similar immunoassay it was shown that in normal individuals serum levels of sHLA-I were neither correlated with serum levels of intact sHLA-I molecules nor were related to the HLA phenotype. In SLE patients the same absence of correlation between free -chains and intact sHLA-I was observed by Bresciani et al [15].…”
Section: Discussionmentioning
confidence: 89%
“…However, in a previous study Puppo et al [36] using a similar immunoassay it was shown that in normal individuals serum levels of sHLA-I were neither correlated with serum levels of intact sHLA-I molecules nor were related to the HLA phenotype. In SLE patients the same absence of correlation between free -chains and intact sHLA-I was observed by Bresciani et al [15].…”
Section: Discussionmentioning
confidence: 89%
“…The mAb HC‐10, which recognizes a determinant expressed on all β 2 m‐free HLA‐B heavy chains and β 2 m‐free HLA‐A10, ‐A28, ‐A29, ‐A30, ‐A31, ‐A32 and ‐A33 heavy chains,17, 18 the LMP2‐specific mAb SY‐1, the TAP1‐specific mAb TO‐1 and the tapasin‐specific mAb TO‐3 were developed and characterized as described 10, 11, 12. The human CD8‐specific mAb 144B (Dako Cytomation, Glostrup, Denmark), human FasL‐specific rabbit polyclonal antibodies (Santa Cruz Biotechnology, Santa Cruz, CA), human Fas (CD95) ‐specific mouse mAb APO‐1 (Dako Cytomation), human IL‐10‐specific goat polyclonal antibodies (R&D Systems, Minneapolis, MN) and LMP1‐specific mouse Ab CS1‐4 (Dako Cytomation) were purchased from the indicated companies.…”
Section: Methodsmentioning
confidence: 99%
“…The mAb HC 10, which recognizes a determinant expressed on all h2-microglobulin-free HLA-B HCs and on h2-microglobulin-free HLA-A10, HLA-A28, HLA-A29, HLA-A30, HLA-A31, HLA-A32, and HLA-A33 HC (15,16); the anti-h2-microglobulin-specific mAb L368 (17) and the mAb TP25.99, which recognizes a conformational determinant expressed on all h2-microglobulin-associated HLA-ABC HC and a linear determinant expressed on all h2-microglobulin-free HLA-B HC except HLA-B73 and on h2-microglobulin-free HLA-A1, HLA-A3, HLA-A9, HLA-A11, and HLA-A30 HC were developed and characterized as described (18). The MB-1-mAb SY-1, the LMP7-specific mAb SY-3, the LMP10-specific mAb TO-7, the TAP2-specific mAb NOB-2, the calnexin-specific mAb TO-5, the calreticulinspecific mAb TO-11, the ERp57-specific mAb TO-2, and the tapasin-specific mAb TO-3 were developed and characterized as described elsewhere (19,20).…”
Section: Methodsmentioning
confidence: 99%